Forever Young Carol Pratl looks over the 30 years of Carolyn Carlson's visionary career - Pratl, Carol (Dance Books Ltd., Alton,Hampshire (UK), 1998)
The career of Carolyn Carlson. PALABRAS CLAVE: Carolyn Carlson, Signes.
Keywords: Carlson, Carolyn -- 1943-